Pelatihan Self Improvement dalam Meningkatkan Kreatifitas Room Management Santri - Rozi, Fathor; Nabila, Izzah Nur; Qudriyah, Faizatul (Lembaga Yasin AlSys, 2023)
There needs to be persuasive efforts so that students, especially female students in the Al-Hasyimiyah area, can become moral, innovative and creative students, especially creative in terms of room management. In its implementation, this service is carried out by involving santri, especially female students with santri status in the Al-Hasyimiyah area, to be trained on how to develop creative ideas in managing rooms properly and correctly so that a safe and comfortable room to live in will be created. This training is carried out through the stages of presenting material, self-improvement training, demonstration or room management practice and trials. Based on the results of the training carried out, it can be concluded that the implementation of the self-improvement training in increasing the creativity of the students' room management above involves taking four main stages, namely the preparation stage, providing training, trial (direct practice) and evaluation. In terms of motivation, dormitory administrators are able to provide stimulants to fellow administrators and students to work together to manage a dormitory that is safe and comfortable for all. Effective communication is a necessity to mobilize other administrators and students to work together to form a conducive dormitory.